Diseño de un plan de marketing para la Asociación de mujeres de Cumbayá, como medio generador de recursos para sostener sus servicios de labor social - Corral Rodríguez, María Sol (2015)
This research is made in order to design a marketing plan for the Association of Women of the Parish of Cumbayá, an nonprofit institution dedicated to training entrepreneurs women through social assistance. The goal is to give this organization the opportunity to promote their work, organize its administrative structure and promote it both within and outside the parish, by presenting an analysis of its internal and external customers, key competitors, suppliers and donors, identifying its main strengths and opportunities and presenting strategies to combat their weaknesses and threats. As a first step, the current situation and development of the Association since its foundation will be analyzed, identifying the main causes and effects that have caused the decline in income. All theoretical fundaments mentioned herein serve to identify behaviors of current and potential customers of the Association and subsequently design objectives, strategies and tactics to be implemented to generate income to the Association. The request for support from public and private entities, the creating of new training topics, the diffusion of activities and the creation of new programs will serve for the reorganization of the Association. This issues focus on national projects submitted to the gobernment for the generation and promotion of development social activities.